Combined optimization of heat and space for industrial and commercial energy storage pack - Qi Zhou; Bingyun Jiang; Feifei Lu; Hongqing Li (Results in Engineering)
Lithium battery is an important way of energy storage in human daily life. The energy storage pack is now widely used in the power generation side, the grid side and the power side. In order to improve the heat dissipation efficiency and uniformity of air cooling system, an industrial and commercial energy storage pack is studied. To optimize this system, electrochemical-thermal-hydromechanical model and SHERPA algorithm are applied. The accuracy of model and robustness of algorithm are discussed in the article. The combination of thermal optimization and space optimization is considered in this paper. It can effectively prevent cost waste caused by single thermal optimization, and even reduce the raw material cost of the product. In this work, the temperature difference of pack is optimized by 10 %, the volume of pack is optimized by 3 % and the cost of raw materials is optimized by 3.6 %. This work proposed an optimization direction combining heat and space, which is of sufficient reference significance.